MAKNA TRADISI SEKURA CAKAK BUAH - Sari, Eka Purnama; Budijanto, Budijanto; Susilo, Singgih (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2020)
Abstract: Sekura Cakak Buah is the oldest tradition of saibatin community in Lampung Barat regency. The tradition that were born and developed in tandem with the civilization of the people certainly have profound meaning and values. This research aims to uncover and explore the meaning and value of sekura cakak buah tradition for indigenous saibatin communities and to undestand the implementation of meanings and values of tradition in the lives of saibatin community. The study used qualitative design with an understanding approach to the meaning of ethnography. Data were analyzed by analizing domains, taxonomik, components and cultural theres. The results of the study showed that the meaning of sekura cakak buah tradition for the saibatin community is self-identity, life, and sosial life. The meaning and values are implemented in community?s lives which are namely cultural meaning and values including: self identity, cultural heritage, and regional icon; the meaning and value of religion includes the almighty god, praying, giving thanks and ngejalang (forgiving each other; the meaning and values of the economy include activities in the Pasar Tumpah dan Lamban Sekura; as well as the meaning and social values including kinship and relatives, equality between fellow being, beguai jejama (working together) and social relationship of saibatin community.Abstrak: Sekura Cakak Buah merupakan tradisi tertua masyarakat saibatin di kabupaten Lampung Barat. Tradisi yang lahir dan berkembang beriringan dengan peradaban masyarakatnya tentu memiliki makna dan nilai yang mendalam. Penelitian ini bertujuan mengungkap dan menggali makna dan nilai tradisi sekura cakak buah bagi masyarakat adat saibatin, dan memahami implementasi makna dan nilai tradisi dalam kehidupan masyarakat saibatin. Penelitian ini menggunakan desain kualitatif dengan pendekatan pemahaman makna etnografi. Data dialisisis dengan analisis domain, taksonomi, komponen, dan tema budaya. Hasil penelitian menunjukkan bahwa makna tradisi sekura cakak buah bagi masyarakat saibatin adalah identitas diri, kehidupan, dan kehidupan sosial masyarakat. Makna dan nilai tradisi terimplementasi dalam kehidupan masyarakat yang tercakup dalam makna dan nilai budaya, meliputi identitas diri, warisan budaya, dan ikon wilayah; makna dan nilai religi (keagamaan), meliputi Ketuhanan Yang Maha Esa, berdoa, bersyukur, berserah, dan ngejalang (saling memaafkan); makna dan nilai ekonomi, meliputi aktivitas di Pasar Tumpah, dan Lamban Sekura; makna dan nilai sosial, meliputi kekeluargaan dan kekerabatan, kesamaan antar sesama, beguai jejama (bekerja sama) dan hubungan sosial masyarakat saibatin.